Understanding Possible Roles of Locally-grown Ethnic Produce in Dietary Practices and Food Cultures: An Exploratory Study. Issue 1 (2nd January 2016) - Goto, Keiko; Whitten, Jennifer; Giovanni, Maria; Wolff, Cindy; Bianco, Stephanie
Abstract : The objective of this study was to explore possible roles of locally-grown ethnic produce in dietary practices and food cultures in rural northern California. Four focus groups were conducted with Hmong, Mexican, and white participants (N = 24). Focus group results indicate that availability and accessibility of fresh ethnic produce may be a key to preservation of traditional food practices among ethnic groups. Focus groups also revealed that sharing food cultures across different groups through ethnic produce promotion at farmers' markets may contribute to both openness to other food cultures and preservation efforts of traditional food practices.